IoT Based Remote Low Voltage Power Circuit Breaker System in Flood Areas - Syafitri, Ainil; Syarif, Kemil (Fakultas Teknik Universitas Pancasila, 2024)
In some housing complexes with traditional electrical installation systems, electrical substations are often located in the middle of the housing complex or an area affected by flooding, causing the substation to be submerged and potentially endangering flood victims from being electrocuted. Based on these conditions, a remote voltage breaker system is needed to cut the electricity off automatically when the water level has passed a set point. This remote low-voltage electricity breaker system in flood areas is a tool for disconnecting the electrical system by detecting the water level. It can be monitored remotely based on IoT using an Android-based application. Using the HCSR04 Ultrasonic sensor to detect the water level in each container with a reading distance ranging from 2 cm to 450 cm, Ultrasonic sensor measurements will determine whether the detected water level is dangerous or not if the condition is dangerous, namely the detected water level is higher than the set point. Then, the MCCB will trip automatically. A microcontroller will process data and display the water level on the smartphone using the Blynk application. This tool uses a Node MCU-type microcontroller equipped with an ESP8266 WiFi module that functions as a regulator of the components used. The Blynk application will display water level monitoring data detected by the ultrasonic sensor in centimetre units. In the Blynk application, there is also a widget button that triggers the MCCB manually remotely. Several tests carried out on ultrasonic sensors produce the lowest error value of 1.49%, and the maximum trip time is 2.07 seconds.